2015
DOI: 10.1111/hae.12765
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and management of pain in children and adolescents with bleeding disorders: a cross‐sectional study from three haemophilia centres

Abstract: As the intensity of pain in on-demand patients was highest, using prophylaxis treatment is suggested. Moreover, adolescent patients reported more pain; giving more self-care information to them and their parents is recommended. Since little evidence was published for pain assessment and management in children and adolescents with bleeding disorders, more research is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 27 publications
4
34
0
Order By: Relevance
“…Pain in children with haemophilia is probably unrecognized and under treated. A recent study revealed that 20.8% of children and adolescents with bleeding disorders suffered from moderate pain most commonly involving joints in a non‐acute bleeding state this may impact on functional ability and HRQoL. In our cohort, 26% of boys reported pain in the Haemo‐QoL SF in the last six months.…”
Section: Discussionmentioning
confidence: 61%
“…Pain in children with haemophilia is probably unrecognized and under treated. A recent study revealed that 20.8% of children and adolescents with bleeding disorders suffered from moderate pain most commonly involving joints in a non‐acute bleeding state this may impact on functional ability and HRQoL. In our cohort, 26% of boys reported pain in the Haemo‐QoL SF in the last six months.…”
Section: Discussionmentioning
confidence: 61%
“…Healthcare professionals are known to have poor recognition and understanding of pain management in children with haemophilia . A recent publication by Tagliaferri et al concurs that pain is under‐recognized and unsatisfactorily addressed, with discrepant clinician and patient views.…”
Section: Discussionmentioning
confidence: 99%
“…One likely assumption is that parents of children with current inhibitors might report even higher scores of the HEMOCAB. However, children with past inhibitors could have target joints and chronic pain (Rambod, Forsyth, Sharif, & Khair, ; Vulpen, Holstein, & Martinoli, ) which may increase the burden for the parent (DeKoven, Karkare, Lee, et al, ).…”
Section: Discussionmentioning
confidence: 99%